Analisis Penerapan Sistem Pengendalian Internal Pemberian Kredit Pada Koperasi Simpan Pinjam Karya Abadi Kecamatan Sekayu - Deswati Supra; Jumania Setpariani; M. Rengga Ramanda (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
This study aims to implement an internal control system for providing credit at the Karya Abadi Savings and Loan Cooperative, Sekayu District. The data used in this study is primary data in the form of interviews. The research method used is a qualitative method. Data collection techniques used by the author are interviews, documentation and literature study. The data analysis technique used in this study is a quantitative technique. The theory used is the theory of internal control and credit. The results of this study indicate that the internal control carried out by KSP Karya Abadi Sekayu, has fulfilled all the elements of internal control, but in its implementation the internal control is not optimal.